URGENSI KEWENANGAN CONSTITUTIONAL COMPLAINT SEBAGAI UPAYA MEMPROTEKSI HAK KONSTITUSIONAL WARGA NEGARA INDONESIA OLEH MAHKAMAH KONSTITUSI - , Meggi Salay, Joko Setiono, S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This minithesis entitled âThe Urgency of Constitutional Complaint Authority as Effort to Protect Constitutional Rights of Indonesian Citizen by Constitutional Court.â The purpose of this research was to know and gain data concerning on the problem studied by authors, i.e.: 1) What is the urgency of Constitutional Complaint authority owned by Constitutional Court?, 2) How is the synchronization of Constitutional Complaint by Indonesia legal state?, 3) Whether Constitutional Complaint is needed by Indonesian Citizen of which can not be disturbed by the action of stateâs authority? The way of finding out necessary data was by conducting interview directly to Research Centre of Constitutional Constitution as the representative of Head of Constitutional Court Mr. Moh. Mahfud, MD. The conclusion of the author is, based on the authority given to Constitutional Court based on the Article 24 C of Constitution of 1945, thus Constitutional Court has no rights to examine and decide on Constitutional Complaint. In the case government gives no such kind of authority to Constitutional Court thus the violation of constitutional rights of citizen will keep on going